A Practical Guide to Queering the Adult English Language Classroom. Issue 4 (November 2019) - Rhodes, Christy M.
There are few places more open and inclusive than an adult English language class. Or, are there? Although adult educators teaching in these multi-cultural and linguistically heterogeneous environments use practices designed to embrace their students' diverse ethnic and linguistic identities, they less frequently incorporate practices to be inclusive of another important element students bring into the classroom, their sexual identity. Evidence suggests that while educators want to be inclusive, they are reluctant or unsure of how to do so. The purpose of this article is to supply English language teachers of adults with strategies to positively address sexual identity in ways that establish an inclusive environment for all learners.